Learning, adaptive expectations, and technology shocks - Kevin X. D. Huang; Zheng Liu; Tao Zha (Federal Reserve Bank of Atlanta, 2008)
This study explores the macroeconomic implications of adaptive expectations in a standard real business cycle model. When rational expectations are replaced by adaptive expectations, we show that the self-confirming equilibrium is the same as the steady-state rational expectations equilibrium for all admissible parameters but that dynamics around the steady state are substantially different between the two equilibria. The differences are driven mainly by the dampened wealth effect and the strengthened intertemporal substitution effect, not by the escapes emphasized by Williams (2003). As a result, adaptive expectations can be an important source of frictions that amplify and propagate technology shocks and seem promising for generating plausible labor market dynamics.
Keywords: E32; 330; self-confirming equilibrium; amplification; labor market dynamics; wealth and substitution effects; hump-shaped responses; Real Business Cycle; Adaptive Erwartung; Lernprozess; Technischer Fortschritt; Schock; Theorie